2021
DOI: 10.1021/acsomega.1c01639
|View full text |Cite
|
Sign up to set email alerts
|

A Multiwalled Carbon Nanotube-Based Polyurethane Nanocomposite-Coated Sand/Proppant for Improved Mechanical Strength and Flowback Control in Hydraulic Fracturing Applications

Abstract: A novel resin-based nanocomposite-coated sand proppant is introduced to address the issue of proppant flowback in post-fracturing fluid flowback treatments and hydrocarbon production. Self-aggregation in the water environment is the most attractive aspect of these developed proppants. In this work, sand was sieve-coated with 0.1% multiwalled carbon nanotubes (MWCNTs) followed by optimized thin and uniform resin (polyurethane) spray coating in the concentration range of 2 to 10%. Quantitative and qualitative ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…As shown in Figure 3 a, the T deg for microsand-PS-PMMA/DVB is determined to be 350 °C while that of microsand-(PS-PMMA/DVB)-(Epoxy-CG) was found to increase to 370 °C. At the same time, the T deg for microsand-epoxy is found to be only 345 °C The observed thermal stability values are found to be much higher than that of various other resin systems including furan [ 53 ], phenolic [ 54 ], polyurethane [ 33 , 53 ], polyurethane-carbon nanostructure composites [ 38 ] reported in the literature ( Table 1 ). This thermal stability enhancement of the dual-coated microsand proppants can be accredited to the improved thermal stability of the Epoxy-CG composite layer which is in turn credited to the thermal stability of graphene nanosheets.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…As shown in Figure 3 a, the T deg for microsand-PS-PMMA/DVB is determined to be 350 °C while that of microsand-(PS-PMMA/DVB)-(Epoxy-CG) was found to increase to 370 °C. At the same time, the T deg for microsand-epoxy is found to be only 345 °C The observed thermal stability values are found to be much higher than that of various other resin systems including furan [ 53 ], phenolic [ 54 ], polyurethane [ 33 , 53 ], polyurethane-carbon nanostructure composites [ 38 ] reported in the literature ( Table 1 ). This thermal stability enhancement of the dual-coated microsand proppants can be accredited to the improved thermal stability of the Epoxy-CG composite layer which is in turn credited to the thermal stability of graphene nanosheets.…”
Section: Resultsmentioning
confidence: 85%
“…These long-standing drawbacks of RCPs are partly resolved by coating the frac sand with polymer nanocomposites [ 35 , 36 , 37 ]. Due to their mechanical properties, the combination of these materials with other nanofillers such as carbon nanotube, graphene, and graphene oxide (GO) has been able to improve the thermo-mechanical stabilities of the proppants [ 28 , 35 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GNPs and MWCNTs reinforcement enhanced the stress resistance for these glass beads and sand proppants. This improvement in stress resistance can be attributed to the mechanical reinforcement provided by GNPs and CNTs to the polyurethane resin coating; indeed, nanofiber coatings (which have a high aspect ratio) provide extra mechanical strength to the resin. In conclusion, their demonstrated stress resistance improvement makes GNPs-RCP and MWCNTs-RCP potential candidates for hydraulic fracturing operations.…”
Section: Resultsmentioning
confidence: 98%
“… 37 Proppants appear to undergo substantial proppant pack compaction and porosity reduction due to the strong in situ confining stresses that occur underground. 38 The embedment of proppants leads to the decrease of conductivity. However, the fracture conductivity test has shown that the conductivity of UDP propped fracture is higher than that of quartz sand and ceramsite under high closing stress.…”
Section: Resultsmentioning
confidence: 99%